Classifying Desirable Features of Software Visualization Tools for Corrective Maintenance - Sensalire, Mariam; Ogao, Patrick; Telea, Alexandru (ACM symposium on Software visualization, 2008)
We provide an evaluation of 15 software visualization tools applicable to corrective maintenance. The tasks supported as well as the techniques used are presented and graded based on the support level. By analyzing user acceptation of current tools, we aim to help developers to select what to consider, avoid or improve in their next releases. Tool users can also recognize what to broadly expect (and what not) from such tools, thereby supporting an informed choice for the tools evaluated here and for similar tools.
Keywords: Software Visualization Tools; Corrective Maintenance